A multivalent nanobody–drug conjugate to prevent and treat influenza virus infections - Thibault J. Harmand; Laura Pietrok; Helen Rich; Rhogerry Deshycka; Laney Flanagan; Aaron Accardo; Novalia Pishesha; Hidde L. Ploegh (Proceedings of the National Academy of Sciences, 2025)
We describe the production and use of nanobody drug conjugates that comprise of VHH kappa , a nanobody that recognizes mouse immunoglobulin kappa light chains, and one or more copies of the small molecule influenza virus neuraminidase (NA) inhibitor, zanamivir. Such compounds achieve half-life extension of zanamivir, while recruiting polyclonal immunoglobulins of all isotypes regardless of specificity to infected cells for antibody-dependent cell-mediated cytotoxicity and complement-dependent cellular cytotoxicity. Since the influenza A virus (IAV) NA is a tetramer, we produced VHH kappa adducts with 1, 2, or 4 zanamivir molecules attached in a site-specific manner, to allow multivalent engagement of NA. Administration of a VHH kappa adduct modified with 4 zanamivir molecules (VHH kappa –Zan 4 ) was ~10-fold more potent in protection against infection with IAV than VHH kappa –Zan carrying only a single zanamivir molecule. VHH kappa –Zan 4 can be given intranasally to confer full protection against a lethal IAV challenge. The neutralizing antibody titers in the respiratory mucosa and in the circulation, as well as the serum IgG antibody response against the hemagglutinin and nucleoprotein, are higher in VHH kappa –Zan 4 treated mice that survived the lethal challenge than in controls infected with a sublethal dose of virus. VHH kappa –Zan 4 affords protection even when given intranasally weeks prior to a challenge with a lethal dose of IAV. This type of adduct can therefore be applied prophylactically and therapeutically and does not require prior immunization for protection against a lethal dose of IAV.